Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1007/s12094-016-1582-1
|View full text |Cite
|
Sign up to set email alerts
|

miR-26a-5p suppresses tumor metastasis by regulating EMT and is associated with prognosis in HCC

Abstract: Downregulation of miR-26a-5p promotes tumor metastasis by targeting EMT and influences the prognosis of HCC patients. Therefore, miR-26a-5p has potential as a new biomarker and therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 43 publications
1
31
0
Order By: Relevance
“…miRNAs have a critical role in the biological behavior of liver cancer (23). Various studies have indicated the effectiveness of miRNAs against HCC and HB is due to their ability to inhibit cell growth, invasion ability, angiogenesis and induce tumor cell apoptosis (24)(25)(26)(27). miR-378a has been reported to regulate multiple physiological activities, including myoblast differentiation, adipogenesis, and tumor growth (28), such as those found in colorectal cancer and rhabdomyosarcoma (19,(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs have a critical role in the biological behavior of liver cancer (23). Various studies have indicated the effectiveness of miRNAs against HCC and HB is due to their ability to inhibit cell growth, invasion ability, angiogenesis and induce tumor cell apoptosis (24)(25)(26)(27). miR-378a has been reported to regulate multiple physiological activities, including myoblast differentiation, adipogenesis, and tumor growth (28), such as those found in colorectal cancer and rhabdomyosarcoma (19,(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al found that p53 mediated activation of miR-26a induced apoptosis in HCC cells [175]. Furthermore, low expression of miR-26a correlated with a poor prognosis of HCC patients [144,176]. This finding was also confirmed in patients with HBV-induced HCC [177].…”
Section: Microrna-26amentioning
confidence: 86%
“…However, in the same study, miR-26a promoted HCC tumor cell migration, invasion and metastasis in vivo after injection of tumor cells into the tail vein of nude mice, probably by downregulation of phosphatase and tensin homolog (PTEN) [150]. Other studies also showed that a low amount of miR-26a in HCC leads to activation of the Wnt/β-catenin pathway, reduced E-cadherin expression and induction of epithelial to mesenchymal transition (EMT) [144,145]. Therefore, in contrast to early cancer development, miR-26a might also have oncogenic functions in advanced tumor stages and metastasis in HCC and other types of cancer ( Figure 5).…”
Section: Microrna-26amentioning
confidence: 87%
See 2 more Smart Citations